PENGARUH GAYA KEPEMIMPINAN, MOTIVASI KERJA TERHADAP KOMITMEN ORGANISASI YANG BERIMPLIKASI PADA KINERJA KARYAWAN - Bagus Putu Fabio; Musa Hubeis; Herien Puspitawati (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2016)
The purposes of the study were: (1) to analyze the influence of leadership style and work motivation on organizational commitment; (2) analyze the influence of leadership style, employee motivation, and organizational commitment to employee performance; (3) analyze the effect of leadership style on job motivation; (4) analyze the effect of work motivation on leadership style. The data were collected by using questionnaire with 81 respondents, and subsequently processed by the method of Structural Equation Modelling of Lisrel Program. The results of the study showed that leadership style has the most influencing impact regarding the indicators of the reward explanation. Work motivation which has the most influencing impact is the pride indicators in completing works. The organizational commitment which has the most influencing impact is the indicator of the organization boasts to others. Performance which has the most influencing impact is indicated by the ability to cooperate with others. Thus, leadership style has a greater influence on organizational commitment than on performance. Work motivation also has a greater influence on organizational commitment than on performance. The organizational commitment has the most impact on performance compared to the leadership style and motivation, while leadership style has a greater influence on work motivation than work motivation on leadership styles.Keywords: leadership style, employee performance, organizational commitment, work motivation